THE EFFECT OF DISCUSSION TECHNIQUE AND ENGLISHLEARNINGMOTIVATIONTOWARD STUDENTS’ SPEAKING ABILITY - Menggo, Sebastianus (STKIP Santu Paulus Ruteng, 2016)
Abstract: The Effect Of Discussion Technique and English Learning Motivation Toward Students’ Speaking Ability. The aim of this study is to investigate (1) whether there is a difference in the speaking abilitybetween students who are taught by usingdiscussion technique and those taught by using the conventional technique; (2) an interactional effect between the speakingtechniques applied and English learning motivation toward students’ speaking ability; (3) a difference in speaking ability between students with high English learning motivation who are taught by using discussion technique and those taught by using the conventional technique; and (4) a difference in speaking ability between students with low English learning motivation who are taught by using discussion technique and those taught by using the conventional technique. The study used a 2X2 factorial design, which involved a sample of 124 students. The data were collected by using questionnaire and a speaking test then analyzed by Two-way ANOVA. The result indicates that (1) there was a significant difference in speaking ability between the students who were taught by using discussion technique and those taught by using the conventional technique; (2) there was a significant interactional effect between the teaching techniques applied and students’ motivation toward their speaking ability; (3) there was a significant difference in speaking ability between students with high English learning motivation who were taught by using discussion technique and those taught with the conventional technique; and (4) there was significant difference in speaking ability between the students with low English learning motivation who were taught by using discussion technique and those taught with the conventional technique. Keywords: discussion technique,motivation, speaking ability Abstrak: Pengaruh Teknik Diskusi dan Motivasi Belajar Bahasa Inggris Terhadap Kemampuan Berbicara Bahasa Inggris. Tujuan dari penelitian ini adalah untuk mengetahui(1) apakah ada perbedaan kemampuan berbicara bahasa Inggris antara siswa yang diajarkan dengan menggunakan teknik diskusi dan siswa yang diajarkan dengan menggunakan teknik konvensional; (2) apakah ada interaksi antara teknik yang digunakan dan motivasi belajar bahasa Inggris terhadap kemampuan berbicara siswa; (3) perbedaan kemampuan berbicara bahsa Inggris antara siswa dengan motivasi tinggi yang diajarkan dengan menggunakan teknik diskusi dan siswa yang diajarkan dengan menggunakan teknik konvensional; dan (4) perbedaan kemampuan berbicara bahasa Inggris dengan motivasi rendah yang diajarkan dengan menggunakan teknik diskusi dan siswa yang diajarkan dengan menggunakan teknik konvensional.Penelitian ini menggunakan desain faktorial 2X2 dengan total sampel penelitiannya124 siswa. Data diperoleh melalui angket dan tes kemampuan berbicara lalu dianalisis dengan menggunakan ANOVA dua jalur. Hasilnya menunjukan bahwa (1) ada perbedaan yang signifikan kemampuan berbicara bahasa Inggris antara siswa yang diajarkan dengan menggunakan teknik diskusi dan siswa yang diajarkan dengan teknik konvensional; (2) ada interaksi antara teknik yang diterapakan dan motivasi siswa terhadap kemampuan berbicara bahasa Inggris ; (3) ) ada perbedaan kemampuan berbicara bahasa Inggris antara siswa dengan motivasi tinggi yang diajarkan dengan menggunakan teknik diskusi dan siswa yang diajarkan dengan menggunakan teknik konvensional; dan (4) ada perbedaan kemampuan berbicara bahasa Inggris antara siswa dengan motivasi rendah yang diajarkan dengan menggunakan teknik diskusi dan siswa yang diajarkan dengan menggunakan teknik konvensional Kata kunci: teknik diskusi, motivasi, kemampuan berbicara